A novel approach to quantifying the degree of anthropogenic surface transformation – the concept of ‘hemeromorphy’ - Rózsa, Péter; Incze, József; Balogh, Szabolcs; Novák, Tibor József (ERDKUNDE, 2020)
The degree of human geomorphological impact was estimated as a ratio of natural geomorphological processes and geomorphological processes triggered or facilitated by humankind. A typical Central European cultural landscape of diverse land use and relief was considered as a pilot area. Based on topography maps and landforms the natural material fluxes were calculated. By overlapping historical maps, modern maps and remotely sensed data, the duration and extent of different land use types were mapped, and were assigned to each landscape unit. Anthropogenic material fluxes were calculated for the land use types identified. Dividing the summarized anthropogenic material fluxes by natural ones, the anthropic geomorphological transformation ratio (rAG) was estimated. The value of rAG is independent of the efficiency and intensity of processes; it merely expresses the relation of effectiveness between human induced and natural processes. Since the calculated index is based on estimated values and there is, at least theoretically, no upper limit, the term ‘hemeromorphy’ was introduced and the values were classified in corresponding ‘hemeromorphy’ categories. For the smallest landscape units with the same degree of ‘hemeromorphy’ the term ‘hemeromorphotop’ was applied. This interpretation makes the comparison of landscape units possible according to their anthropogeomorphological transformation, independently of the intensity and quality of their geomorphological processes.